2000
DOI: 10.1074/jbc.m000170200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dichotomy of Protein Kinase C (PKC) in Tumor Necrosis Factor-α (TNF-α) Signal Transduction in L929 Cells

Abstract: Tumor necrosis factor-␣ (TNF-␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 68 publications
3
44
0
Order By: Relevance
“…TNF-a is a membrane-bound molecule that upon de novo synthesis is exported from the trans-Golgi network to the plasma membrane in a protein kinase C (PKC)-dependent manner (Lee et al, 2000;Abdel-Raheem et al, 2005). Once exposed to the plasma membrane, it can be sheded by different metalloproteinases belonging to the TNF-a-converting enzyme family (Mezyk et al, 2003), resulting in the release of soluble TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a is a membrane-bound molecule that upon de novo synthesis is exported from the trans-Golgi network to the plasma membrane in a protein kinase C (PKC)-dependent manner (Lee et al, 2000;Abdel-Raheem et al, 2005). Once exposed to the plasma membrane, it can be sheded by different metalloproteinases belonging to the TNF-a-converting enzyme family (Mezyk et al, 2003), resulting in the release of soluble TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that dephosphorylation of PKCs can occur at sites such as the A-loop and HM in response to stimuli such as Tumor Necrosis Factor-, which is likely to be a key step in turning off the signalling capacity of these kinases [75]. Prolonged PKC signalling that is promoted by phorbol esters or sustained DAG signalling results in downregulation of…”
Section: Dephosphorylation Of Pkcmentioning
confidence: 99%
“…Dephosphorylation of PKCs in cells was initially shown to be sensitive to okadaic acid, which implicated the PP2a-like phosphatases in this process [79,80,75]. More recent studies have identified an additional family of okadaic acidinsensitive phosphatases called PHLPPs that specifically dephosphorylate the HM (but not the TM) of PKCs upon prolonged phorbol ester treatment [81].…”
Section: Dephosphorylation Of Pkcmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Ceramide activates a number of kinases ( Figure 1) including stress-activated protein kinases (SAPKs) such as the jun kinases (JNKs [25][26][27] ), kinase suppressor of Ras (KSR [28][29][30], and the atypical PKC isoform, PKC . [31][32][33] Conversely, ceramide can inhibit kinases such as the classical and novel PKC isoforms (eg PKC ␣ [14][15][16] ) and the PKB kinase, Akt. 29,[34][35][36] The mechanism of kinase inhibition appears to involve ceramide's ability to activate protein phosphatases (Figure 1 and Refs 16,17,[36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…12 Consistent with the notion that DAG and ceramide have counterbalancing effects, DAG can attenuate the effects of ceramide 13 and ceramide can antagonize DAG by inhibiting PKC. [14][15][16] An elegant homeostatic regulatory system is emerging with DAG as a growth positive regulator and ceramide as a negative growth regulator. Since each effector is able to transmodulate the signaling pathways regulated by the other, it is possible that net expression of DAG vs ceramide may create a sort of cellular rheostat.…”
Section: Introductionmentioning
confidence: 99%